Motor learning of mice lacking cerebellar Purkinje cells - Armengol, José A.; Porras, Elena; Ruiz, Rocío; Pérez-Villegas, Eva Mª (Frontiers in Neuroanatomy, 2013)
The cerebellum plays a key role in the acquisition and execution of motor tasks whose physiological foundations were postulated on Purkinje cells' long-term depression (LTD). Numerous research efforts have been focused on understanding the cerebellum as a site of learning and/or memory storage. However, the controversy on which part of the cerebellum participates in motor learning, and how the process takes place, remains unsolved. In fact, it has been suggested that cerebellar cortex, deep cerebellar nuclei, and/or their combination with some brain structures other than the cerebellum are responsible for motor learning. Different experimental approaches have been used to tackle this question (cerebellar lesions, pharmacological agonist and/or antagonist of cerebellar neurotransmitters, virus tract tracings, etc.). One of these approaches is the study of spontaneous mutations affecting the cerebellar cortex and depriving it of its main input–output organizer (i.e., the Purkinje cell). In this review, we discuss the results obtained in our laboratory in motor learning of both Lurcher (Lc/+) and tambaleante (tbl/tbl) mice as models of Purkinje-cell-devoid cerebellum.